Proclamation of the All-Russian Empire – the Beginning of the Way to the Great Power Status - V. A. Artamonov (Vestnik MGIMO-Universiteta, 2022)
Many historians believe that Russia became a great power either as a result of the Poltava victory in 1709, or after the Nystadt Peace of 1721. It is difficult to agree with this. Peter the Great’s rule indeed produced a combat-ready regular army, a guard, an officer corps, a navy with shipyards, military bases, and coastal artillery. There was an upsurge in the metallurgical industry and mining. Schools with high-quality military and secular education, the Academy of Sciences, the Senate, and the Synod were established. St. Petersburg was founded. Talented and enterprising individuals were promoted to military, diplomatic and administrative posts. The main factor in the rise of the state was military modernization. The main geopolitical achievement of Peter I was the conquest of full access to the Baltic Sea. However, a limited resource base, military and diplomatic defeats and setbacks did not allow Russia to rise to the rank of a great power. The disasters of Narva in 1700 and on the Prut River in 1711 were painful. Russia lost access to the Sea of Azov, the city of Azov, city of Taganrog, the Azov squadron, shipyards and shipbuilding in the Voronezh Territory were lost. The damage from three treatises with the Ottomans in 1711-1713 was great. Russia has lost all of Zaporozhye. The demarcation of the borders of 1714 threw Russia back several hundred kilometers from the Black Sea region. In 1719, the Russian military force was squeezed out of Central Europe – from Mecklenburg. The sphere of influence of Russia after the victorious Peace of Nystad in 1721 was established only in Northern and Eastern Europe – in the Polish-Lithuanian Commonwealth, the Swedish and Danish-Norwegian kingdom, partly in Prussia. The tsar had no claims to hegemony in Europe and no claims to join the circle of the then great powers. Russia was not a great power like the Habsburg monarchy, France, Great Britain, and the Eurasian-African Ottoman Empire. Russia could not compare with the great powers of that time neither in terms of economic (industrial, financial) power, nor in terms of the intensity of expansionism. The entry of the Russian Empire into the system of international relations as one of the five great powers – France, Great Britain, Austria, Prussia, and Russia – occurred during the Seven Years War of 1756-1763. Another rise to great power took place during the reign of Catherine II. The apogee of greatness and the culmination of Russia's influence on European affairs was the Congress of Vienna in 1814-1815.